Plate configuration for biological reconstructions of femoral intercalary defect - a finite element evaluation. (September 2022) - He, Ziyang; Huang, Siyi; Ji, Tao; Tang, Xiaodong; Yang, Rongli; Guo, Wei
Highlights: Optimizing plate configurations for better mechanical stability during biological reconstruction for large femoral diaphysis defect by finite element analysis. Parallel opposed plates covering full length of defect showed superior stability under vertical compression and optimal torsion stability with an axial moment. Adequate stability is believed to be essential for bone union and reduced risk of implant failure. Abstract: Background and objective: Biological reconstruction was commonly used for femoral intercalary defect. The initial stability by plate fixation was believed to have an effect on bone union and implant failure. Our study was proposed to explore relationship of plate configuration and initial stability for femoral intercalary reconstruction using allo-/autograft. Methods: Femoral intercalary defect models were established with four different plate configurations: (1) Single lateral bridging plate, SLP (2) Lateral bridging plate + Orthogonal adjuvant plate, LP+OAP (3) Lateral bridging plate + Medial adjuvant plate, LP+MAP (4) Lateral bridging plate + Medial bridging plate, LP+MP. A diaphysis defect of 12 cm was simulated, and the removed native femoral bone was used as a structural allograft with the osteotomy gap of 2 mm. Models were analyzed by finite element simulations under an axial compression of 2000N and an axial moment of 10 Nm, respectively. Results: Axial load: (1) The peak von Mises stress of SLP, LP+OAP, LP+MAP, LP+MP were 993.50 MPa, 335.63 MPa, 240.03 MPa, 281.73 MPa, respectively and LP+MAP was the lowest ( p < 0.01); (2) The mean displacement of SLP, LP+OAP, LP+MAP, LP+MP was 0.765, 0.130, 0.121, 0.235 mm, respectively. LP+MAP showed the best stability while SLP had a crash in the medial proximal gap; (3) The LP+MAP configuration had the most uniform stress distribution and the lowest maximum von Mises stress of 79.7 MPa within plates. Axial torsional load: (1) The peak von Mises stress of SLP, LP+OAP, LP+MAP, LP+MP were 431.66Mpa, 120.73 MPa, 72.31 MPa, 109.86 MPa, respectively; (2) The rotation angle of SLP, LP+OAP, LP+MAP, LP+MP was 4.30°, 1.35°, 1.20°, 1.57°, respectively. All of LP+OAP, LP+MAP and LP+MP showed an optimal torsional stability. Conclusions: For femoral intercalary reconstruction using allo-/autograft fixed by plates, LP+MAP and LP+MP configurations showed superior stability in terms of axial compression and torsion load by FE simulation. A better stability was believed to be associated with higher union rate and lower hardware failure rate.